Evolving Experimental Platforms to Evaluate Ulcerative Colitis (Adv. Biology 10/2022). Issue 10 (21st October 2022) - Sharma, Tiffany T.; Rabizadeh, Rebecca R.; Prabhakar, Vibhav S.; Bury, Matthew I.; Sharma, Arun K.
Abstract : Evaluation Ulcerative Colitis In article 2200018, Sharma and co‐workers meet approaches to mitigate inflammation observed in ulcerative colitis (UC) together with numerous technological challenges. Severe UC predisposes to poor clinical outcomes and lower health‐related quality of life. The timely delivery of biocompatible anti‐inflammatory nanofibers in the form of supramolecular peptide amphiphiles can positively modulate protracted tissue inflammation in UC due to its innate molecular packing and saturating abilities.